The Role of Professional Training in Developing Leadership Skills Among Information Technology Sector Employees - Aizza Anwar; Rashmi Chaudhary; Nur Anis Najihah Binti Aziz; Nur Anis Athirah Binti Azhar; Nur Anis Athirah Binti Azhar; Nur Anisah Sakinah Binti Mohamed Elias; Nur Arisya Binti Azhar; Pallavi Mittal; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
As technology advances, the professional world is becoming increasingly competitive. Achieving career success and meeting professional goals now requires both new and seasoned employees to continuously develop their skills and expand their knowledge. This necessity highlights the importance for businesses in the IT sector to expose their employees to professional training programs that enhance leadership skills, ultimately benefiting the organization. The main aim of this study is to examine the impact of professional training on leadership skills development among IT sector employees, focusing on the challenges and benefits identified through a qualitative approach. Data was collected via a survey questionnaire, with responses from 200 participants in Malaysia and India. The findings reveal the impact of professional training for IT employees, particularly regarding the role of training activities in fostering leadership development. This study offers insights and guidance for employees on the advantages and obstacles of pursuing professional training, leading to enhanced leadership capabilities.